In-shoe measurement for biomechanical monitoring - Billing, D.; Hayes, J. (2007)
The purpose of the research is to investigate the measurement and characterisation of biomechanical variables associated with ground contact during the course of athletic activity (e.g., running). The measurement approach will involve the appropriate instrumentation of a shoe insole, which lies between the foot and the shoe bed, using MicroElectroMechanical Stucture (MEMS) based sensors. The information obtained from the insole could be used to quantify training stress and competition demands which will greatly assist in enhancing athletic performance. This research will be carried out between the years of 2001 and 2004, under a collaboration between the Industrial Research Institute of the Swinburne University of Technology (IRIS), the Australian Institute of Sport (AIS) and the Cooperative Research Centre (CRC) for MicroTechnology.